The pyrolytic evolution of morphology in biobased coke replacement briquettes: Links between morphology, nanowire characteristics, and performance in cupolas. (December 2018) - Peña, L.; Mitchell, G.; Cannon, F.S.; Komarneni, S.; Brown, N.R.
Abstract: A morphological study of lignin-bound anthracite briquettes was carried out to understand the mechanisms that hold together anthracite fines and silicon grains at elevated temperatures and high abrasion conditions. Lab-scale briquettes were prepared from anthracite fines, lignin, collagen, silicon, and other additives; and then pyrolyzed at 800 °C, 1400 °C and 1600 °C under nitrogen atmosphere to simulate the conditions inside a foundry cupola. The pyrolyzed samples were analyzed by reflected light microscopy, electron microscopy and x-ray diffraction. These analyses gave information on the transformations that lignin-bound anthracite briquettes may undergo in a cupola furnace. Lignin and collagen melted and formed an amorphous carbon phase that linked anthracite and silicon grains. Silicon carbide (SiC) nanowires coated in silicon oxide were formed at 1400 °C, and at 1600 °C most of the silicon was converted to SiC. Silicon carbide nanowires filled the interstitial voids left by volatilization of lignin and collagen. These findings support the idea that lignin and collagen hold anthracite fines at low temperature regimes. Silicon carbide nanowires contribute to briquette strength at high temperature conditions, acting as reinforcing filler and prevent collapse of the lignin-collagen matrix surrounding the anthracite grains. Graphical abstract: Image 1